2023
DOI: 10.3390/antib12040069
|View full text |Cite
|
Sign up to set email alerts
|

When Autoantibodies Are Missing: The Challenge of Seronegative Rheumatoid Arthritis

Marino Paroli,
Maria Isabella Sirinian

Abstract: Seronegative rheumatoid arthritis (SNRA) is characterized by the absence of both rheumatoid factor (RF) and antibodies against the cyclic citrullinated protein (ACPA) in serum. However, the differences between the two forms of RA are more complex and have not yet been definitively characterized. Several lines of evidences support the idea that there are specific elements of the two forms, including genetic background, epidemiology, pathogenesis, severity of progression over time, and response to therapy. Clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 108 publications
0
1
0
Order By: Relevance
“…This observation is also in keeping with differences in the age of onset found by Carbonell-Bobadilla et al, who reported a higher age at diagnosis in seronegative (54 ± 11 years) vs. seropositive patients (43 ± 14 years) [20]. Furthermore, since cigarette smoking is a well-known enhancer of increased peptidyl arginine deaminase 2, which in turn leads to protein citrullination, an overall reduction in the smoking habits in the population may be an additional explanation of the lower prevalence of ACPA-positive RA [21].…”
Section: Epidemiology Genetics and Clinical Phenotypes: Similarities ...mentioning
confidence: 91%
“…This observation is also in keeping with differences in the age of onset found by Carbonell-Bobadilla et al, who reported a higher age at diagnosis in seronegative (54 ± 11 years) vs. seropositive patients (43 ± 14 years) [20]. Furthermore, since cigarette smoking is a well-known enhancer of increased peptidyl arginine deaminase 2, which in turn leads to protein citrullination, an overall reduction in the smoking habits in the population may be an additional explanation of the lower prevalence of ACPA-positive RA [21].…”
Section: Epidemiology Genetics and Clinical Phenotypes: Similarities ...mentioning
confidence: 91%